'INSPIRE US GENIUS OF THE DAY': REWRITING THE REGENT IN THE BIRTHDAY ODE FOR QUEEN ANNE, 1703. (March 2016) - MURPHY, ESTELLE
ABSTRACT: In 1701–1702 writer and poet Peter Anthony Motteux collaborated with composer John Eccles, Master of the King's Musick, in writing the ode for King William III's birthday. Eccles's autograph manuscript is listed in the British Library manuscript catalogue as 'Ode for the King's Birthday, 1703; in score by John Eccles' and is accompanied by a claim that the ode had already reached folio 10v when William died, requiring the words to be amended to suit his successor, Queen Anne. A closer inspection of this manuscript reveals that much more of the ode had been completed before the king's death, and that much more than the words 'king' and 'William' was amended to suit a succeeding monarch of a different gender and nationality. The work was performed before Queen Anne on her birthday in 1703 and the words were published shortly afterwards. Discrepancies between the printed text and that in Eccles's score indicate that no fewer than three versions of the text were devised during the creative process. These versions raise issues of authority with respect to poet and composer. A careful analysis of the manuscript's paper types and rastrology reveals a collaborative process of re-engineering that was, in fact, applied to an already completed work. This article explores the problems of textual versus musical authority embodied in the ode and the difficulties faced by its creators in reworking a piece originally celebrating a foreign male war-hero for a female British queen during a period of political and religious fragility.